The Effect of Stevia Rebaudiana on Serum Omentin and Visfatin Level in STZ-Induced Diabetic Rats. (1st March 2015) - Akbarzadeh, Samad; Eskandari, Fatemeh; Tangestani, Hadis; Bagherinejad, Somaieh Tangerami; Bargahi, Afshar; Bazzi, Parviz; Daneshi, Adel; Sahrapoor, Azam; O'Connor, William J.; Rahbar, Ali Reza
ABSTRACT: Recently the role of adipocytokines in relationship to incidence of diabetes has been demonstrated. One of the medicinal plants that are used in the treatment of diabetes is stevia. This study investigates the effect of stevia on serum omentin and visfatin levels as novel adipocytokines in diabetic induced rats to find potential mechanisms for the anti hyperglycemic effect of stevia. Forty male wistar rats weighing 180–250 g were induced with diabetes by intraperitoneal injection of streptozotocin (STZ). The animals were divided into 5 groups of 8. Rats in group 1 (non-diabetic control) and group 2 (diabetic control) were treated with distilled water, and the rats in the treated groups, group 3 (T250), group 4 (T500), and group 5 (T750) were treated with stevia, gavaged every day at 9 a.m. in doses of 250, 500, and 750 mg/kg, respectively. At the end of the study significant reductions in fasting blood sugar (FBS), the homeostasis model assessment insulin resistance (HOMA-IR), triglyceride (TG), alkaline phosphatase (ALP), and Omentin level were found in groups 3 and 4 in comparison with group 2. Pancreatic histopathology slides demonstrated that stevia extract did not induce any increase in the number of β-cells. The conclusion is that prescription of stevia in the doses of 250 and 500 mg/kg/d decreases the omentin level indirectly via activating insulin sensitivity and lowering blood glucose in STZ-induced diabetic rats.